Development of innovative satellite-based methods for improved PV yield prediction on different time scales for distribution grid level applications (MetPVNet); Entwicklung innovativer satellitengestützter Methoden zur verbesserten PV-Ertragsvorhersage auf verschiedenen Zeitskalen für Anwendungen auf Verteilnetzebene (MetPVNet) - Stefanie Meilinger; Anna Herman-Czezuch; Nicola Kimiaie; Christopher Schirrmeister; Rone Yousif; Stefan Geiss; Leonhard Scheck; Martin Weissmann; Felix Gödde; Bernhard Mayer; Tobias Zinner; James Barry; et al. (Hochschule Bonn-Rhein-Sieg, Internationales Zentrum für Nachhaltige Entwicklung (IZNE), 2021)
In the research project "MetPVNet", both, the forecast-based operation management in distribution grids and as well as the forecasts of the feed-in of PV-power from decentralized plants could be improved on the basis of satellite data and numerical weather forecasts. Based on a detailed network analyses for a real medium-voltage grid area, it was shown that both - the integration of forecast data based on satellite and weather data and the improvement of subsequent day forecasts based on numerical weather models - have a significant added value for forecast-based congestion management or redispatch and reactive power management in the distribution grid. Furthermore, forecast improvements for the forecast model of the German Weather Service were achieved by assimilating visible satellite imagery, and cloud and radiation products from satellites were improved, thus improving the database for short-term forecasting as well as for assimilation. In addition, several methods have been developed that will enable forecast improvement in the future, especially for weather situations with high cloud induced variability and high forecast errors. This article summarizes the most important project results. – – Im Rahmen des Forschungsprojektes 'MetPVNet' konnten sowohl die prognosebasierte Betriebsführung in Verteilnetzen als auch die Erzeugungsprognose von dezentralen PVAnlagen auf der Basis von Satellitendaten und Numerischer Wettervorhersage verbessert werden. Anhand detaillierter Netzanalysen für ein reales Mittelspannungsnetzgebiet konnte gezeigt werden, dass sowohl die Einbindung von Prognosedaten auf Basis von Satelliten und Wetterdaten, als auch die Verbesserung von Folgetagsprognosen auf der Basis numerischer Wettermodelle einen deutlichen Mehrwert für ein prognosebasiertes Engpassmanagement bzw. Redispatch und Blindleistungs-management im Verteilnetz aufweisen. Darüber hinaus wurden Prognoseverbesserungen für das Vorhersagemodell des Deutschen Wetterdienstes durch die Assimilation von sichtbaren Satellitenbildern erreicht, sowie Wolken- und Strahlungsprodukte aus Satelliten verbessert und somit die Datenbasis für die Kurzfristprognose als auch für die Assimilation. Darüber hinaus wurden verschiedene Methoden entwickelt, die zukünftig eine Prognoseverbesserung, insbesondere für Wettersituationen mit hoher wolkenbedingter Strahlungsvariabilität und hohen Prognosefehlern, ermöglichen. In diesem Artikel werden dies wichtigsten Projektergebnisse zusammengefasst.
urn:nbn:de:hbz:1044-opus-60399
Keywords: 550; Distribution grid management; photovoltaics; generation forecast; satelliteproducts; numerical weather prediction; radiation; cloud parameters; reflectance; COD; AOD; radiation variability; spectral influence; Si reference cells; inversion; energymeteorology; Verteilnetzbetriebsführung; Photovoltaik; Erzeugungsprognose; Satellitenprodukte; numerische Wettervorhersage; Strahlung; Wolkenparameter; Reflektanz; COD; AOD; Strahlungsvariabilität; Spektraler Einfluss; Si-Referenzzellen; Inversion; Energiemeteorologie